The Dominance of CRF01_AE and the Emergence of Drug Resistance Mutations Among Antiretroviral Therapy-Experienced, HIV-1-infected Individuals in Medan, Indonesia - Dwi Wahyu Indriati; Adiana Mutamsari Witaningrum; M Qushai Yunifiar; Siti Qamariyah Khairunisa; Shuhei Ueda; Tomohiro Kotaki; Nasronudin Nasronudin; Masanori Kameoka (Acta Medica Indonesiana)
Background: human immunodeficiency virus type 1 (HIV-1) infection is a serious public health threat worldwide. Medan is one example of big cities in Indonesia with a high prevalence of HIV-1 infection; however, quite a limited study had conducted for detecting the circulation of HIV-1 subtypes in Medan. In addition, a serious factor that can implicate the treatment of HIV-1-infected individuals is the emergence of drug resistance mutations. Thus, the information on HIV-1 infection is important to improve the treatment for infected individuals. Methods: sixty-seven antiretroviral therapy-experienced, HIV-1-infected individuals were recruited for this study. HIV-1 pol genes encoding protease (PR genes) and reverse transcriptase (RT gene), as well as env and gag genes, were amplified from DNA derived from peripheral blood samples. HIV-1 subtyping was conducted to study the dominant HIV-1 subtype circulating in the region. In addition, the emergence of drug resistance mutations was analyzed based on the guidelines published by the International Antiviral Society-United States of America (IAS-USA). Results: the dominant HIV-1 subtype found in Medan was CRF01_AE (77.6%). In addition, another subtype and recombinant viruses such as recombinants between CRF01_AE and subtype B (12.2%), subtype B (4.1%), and CRF02_AG (4.1%) were also found. Drug resistance-associated major mutations were found in 21.6% (8/37) of RT genes and 3.1% (1/32) of PR genes studied. Conclusion:our study showed that the dominant subtype found in ART-experienced, HIV-1-infected individuals residing in Medan was CRF01_AE. The emergence of drug resistance mutations in RT and PR genes indicated the importance to monitor the prevalence of drug resistance mutations among HIV-1-infected individuals in Medan.